Performance of the electromagnetic pixel calorimeter prototype Epical-2. (1st January 2023) - Alme, J.; Barthel, R.; van Bochove, A.; Borshchov, V.; Bosley, R.; van den Brink, A.; Broeils, E.; Büsching, H.; Eikeland, V.N.; Groettvik, O.S.; Han, Y.H.; van der Kolk, N.; et al.
Abstract: The first evaluation of an ultra-high granularity digital electromagnetic calorimeter prototype using 1.0–5.8 GeV/c electrons is presented. The 25 × 10 6 pixel detector consists of 24 layers of ALPIDE CMOS MAPS sensors, with a pitch of around 30 μm, and has a depth of almost 20 radiation lengths of tungsten absorber. Ultra-thin cables allow for a very compact design. The properties that are critical for physics studies are measured: electromagnetic shower response, energy resolution and linearity. The stochastic energy resolution is comparable with the state-of-the art resolution for a Si-W calorimeter, with data described well by a simulation model using Geant4 and Allpix 2 . The performance achieved makes this technology a good candidate for use in the ALICE FoCal upgrade, and in general demonstrates the strong potential for future applications in high-energy physics.